Determination and analysis of dispersive optical constant of as deposited and annealed FeS2 thin films. - Abdulhussain Abbas Khadayeir (Al-Qadisiyah Journal of Pure Science, 2017)
Films of FeS2 were prepared by the spray pyrolysis technique onto a substrate heated up 350 0Ct using iron chloride FeCl2 and thiourea CS(NH2)2 solutions with a concentration of 0.1 M. The optical properties of the films were studied using optical absorption measurements in the wavelength range 300-900 nm and confirmed that the annealing temperature has a significant effect on the properties of these films. The optical constants confirm that FeS2 films have an indirect band gap that decreased from 2.1 to 1.95 eV as the annealing temperature increases to 450ÂºC. The dispersion of the refractive index was analyzed using the concept of a single oscillator. The values of oscillator energy Eo were 4.2, 4, and 3.9eV. The dispersion energy Ed were determined to be 52.7, 90.7, and 102.6 eV for the as deposited films and the annealed films at 400 and 450ÂºC, respectively. The increase in the density of localized states Ed causes an expanding in the Urbach tail and consequently decreases the energy gap.